2014
DOI: 10.1002/fam.2270
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the burning behavior of n‐heptane pool fires at high altitude

Abstract: Summary The same configured calorimeters were built in Hefei (99.8 kPa) and Lhasa (66.5 kPa), respectively. Four sizes of round pans with diameters of 10, 15, 20, and 25 cm were adopted to study the effect of high altitude on the burning behavior of liquid pool fires. Analysis on the burning rate obtained in this study and in the literature at different altitudes indicates that pressure fire modeling performs better than radiation fire modeling in correlating the burning intensity (burning rate per unit area) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The mass burning rate was determined by the convective and radiative heat feedback to the fuel. The mass burning rate was found to decrease with a decrease in pressure, as observed by Zhou et al It was reported that the convective heat feedback to the fuel surface primarily affected the fuel evaporation. It was also reported that as the pressure was decreased, the flame height increased.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The mass burning rate was determined by the convective and radiative heat feedback to the fuel. The mass burning rate was found to decrease with a decrease in pressure, as observed by Zhou et al It was reported that the convective heat feedback to the fuel surface primarily affected the fuel evaporation. It was also reported that as the pressure was decreased, the flame height increased.…”
Section: Introductionsupporting
confidence: 52%
“…The decrease in flame height was attributed to the reduced convective heat feedback to the pool. Zhou et al experimentally studied the burning behavior of n ‐heptane pool flame at high altitude. It was reported that the mass burning rate decreases with a decrease in pressure.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The experiments were primarily done in Lhasa (altitude, 3650 m; pressure, P = 64.3 kPa) and Hefei (altitude, 50 m; P = 101 kPa), and a small number of fire tests were performed at three to four altitudes 3,4 and in a low-pressure chamber. [5][6][7][8][9] The fire test fuel was classified into gaseous, 10,11 liquid, 2,[12][13][14] and solid fuel, [15][16][17][18] and similar conclusions have been reached: In higher-altitude areas, the flame height, flame volume, ignition temperature, and ignition time increase, but the burning rate and flame pulsation decrease. The mass burning rate, radiative heat flux, heat release rate, and combustion efficiency in Lhasa were lower than those in Hefei, and the relationship between the burning rate and the ambient pressure could be simulated with the power function.…”
Section: Introductionmentioning
confidence: 86%
“…Zhou et al [37] specified a quasi-steady burning stage of n-heptane from which the mean burning rate was calculated. The .…”
Section: Effects Of Pressurementioning
confidence: 99%